Biopolymers and Their Composites for Drug Delivery: A Brief Review. Issue 1 (16th August 2018) - Gopi, Sreeraj; Amalraj, Augustine; Sukumaran, Nimisha P.; Haponiuk, Józef T.; Thomas, Sabu
Abstract : In recent years, excipient development has become a core area of research in pharmaceutical drug delivery because it influences the formulation development and drug delivery process in various ways. Polymeric drug delivery systems have been of great interest for controlled delivery as they show the great advantage in drug delivery systems because of optimized drug loading and releasing property. Then, the side effects of synthetic polymers far exceed that it leads to some difficulties like they impose dose reduction, treatment delay, or the given therapy is not continuous. With this in mind and together with the need for a protective delivery system for drugs, natural polymeric substances such as biopolymers and their composites are the choice of research as excipient because of their low toxicity, biodegradability, stability, and renewable nature. Furthermore, they have a wide variety of structures, different physiological functions and may provide a variety of biomedical applications, owing to their distinctive properties. The present brief review explores the concept of excipient delivery and the recent advances in both the biopolymers and the methods in the pharmaceutical drug delivery systems.